Comparative evaluation of green tea and chlorhexidine mouthwashes on gingivitis: A randomized controlled trial - Omveer Singh; Vamsi Krishna Reddy; Devina Pradhan; Lokesh Sharma (Journal of Indian Association of Public Health Dentistry, 2019)
Background: Green tea (Camellia sinensis) is one of the most popularly consumed beverages worldwide containing a number of bioactive chemicals, and it is particularly rich in flavonoids which include catechin. It is linked to a lower incidence of some pathological conditions including oral cancer, dental caries, stroke, cardiovascular diseases, and obesity. Aim: The aim of the study was to compare and evaluate the effects of commercially available green tea mouthwash with chlorhexidine mouthwash on gingivitis. Materials and Methods: A 3-week, double-blinded study was conducted on thirty nursing students aged between 18 and 25 years. Plaque status was assessed by plaque index (Silness and Loe 1964) and gingival status was assessed by gingival index (Loe and Silness 1963) at the 14th day and at the 21st day. Statistical analysis was done using the Statistical Package for the Social Sciences version 21. The test used was one-way analysis of variance and repeated measures. The level of significance was kept as P < 0.05. Results: There was a reduction in the gingivitis scores of the participants using green tea mouthwash as compared to chlorhexidine mouthwash and distilled water. Statistically significant differences were observed between distilled water and green tea groups (P = 0.04). Conclusion: The present study showed that green tea mouthwash was found to be more effective than the chlorhexidine mouthwash in reducing extensive levels of gingivitis.